Lateral Extra-articular Tenodesis Alters Lateral Compartment Contact Mechanics under Simulated Pivoting Maneuvers: An In Vitro Study. Issue 11 (September 2021) - Marom, Niv; Jahandar, Hamidreza; Fraychineaud, Thomas J.; Zayyad, Zaid A.; Ouanezar, Hervé; Hurwit, Daniel; Zhu, Andrew; Wickiewicz, Thomas L.; Pearle, Andrew D.; Imhauser, Carl W.; Nawabi, Danyal H.
Background: There is concern that utilization of lateral extra-articular tenodesis (LET) in conjunction with anterior cruciate ligament (ACL) reconstruction (ACLR) may disturb lateral compartment contact mechanics and contribute to joint degeneration. Hypothesis: ACLR augmented with LET will alter lateral compartment contact mechanics in response to simulated pivoting maneuvers. Study Design: Controlled laboratory study. Methods: Loads simulating a pivot shift were applied to 7 cadaveric knees (4 male; mean age, 39 ± 12 years; range, 28-54 years) using a robotic manipulator. Each knee was tested with the ACL intact, sectioned, reconstructed (via patellar tendon autograft), and, finally, after augmenting ACLR with LET (using a modified Lemaire technique) in the presence of a sectioned anterolateral ligament and Kaplan fibers. Lateral compartment contact mechanics were measured using a contact stress transducer. Outcome measures were anteroposterior location of the center of contact stress (CCS), contact force from anterior to posterior, and peak and mean contact stress. Results: On average, augmenting ACLR with LET shifted the lateral compartment CCS anteriorly compared with the intact knee and compared with ACLR in isolation by a maximum of 5.4 ± 2.3 mm ( P < .001) and 6.0 ± 2.6 mm ( P < .001), respectively. ACLR augmented with LET also increased contact force anteriorly on the lateral tibial plateau compared with the intact knee and compared with isolated ACLR by a maximum of 12 ± 6 N ( P = .001) and 17 ± 10 N ( P = .002), respectively. Compared with ACLR in isolation, ACLR augmented with LET increased peak and mean lateral compartment contact stress by 0.7 ± 0.5 MPa ( P = .005) and by 0.17 ± 0.12 ( P = .006), respectively, at 15° of flexion. Conclusion: Under simulated pivoting loads, adding LET to ACLR anteriorized the CCS on the lateral tibial plateau, thereby increasing contact force anteriorly. Compared with ACLR in isolation, ACLR augmented with LET increased peak and mean lateral compartment contact stress at 15° of flexion. Clinical Relevance: The clinical and biological effect of increased anterior loading of the lateral compartment after LET merits further investigation. The ability of LET to anteriorize contact stress on the lateral compartment may be useful in knees with passive anterior subluxation of the lateral tibia.